Investigation into imbalance of Th1/Th2 cells in cirrhotic, hypersplenic rats - Lv, Yunfu (J Int Med Res, 2019)
OBJECTIVES: To evaluate the Th1/Th2 cell profile in spleens of cirrhotic and hypersplenic rats by investigating the expression of Th1-associated chemokine receptors CXCR3, CCR5 and Th2-associated chemokine receptor CCR3. METHODS: Experimental liver cirrhosis and hypersplenism were induced in rats by the intragastric administration of carbon tetrachloride (CCl(4); 40% solution [0.3 ml/100g, twice/week for 8 weeks]) and confirmed by pathology and hemogram. Presence of the three chemokine receptors was investigated by real-time polymerase chain reaction (RT-PCR), immunohistochemical staining, and western blot analysis. RESULTS: By comparison with control animals (n=10), RT-PCR demonstrated that CXCR3 and CCR5-mRNA levels were significantly elevated in the hypersplenic rats (n=26) and CCR3-mRNA levels were lower. Immunohistochemical staining showed that by comparison with controls, the mean density of the Th1-associated CXCR3 and CCR5 receptors was significantly increased but there was no difference between groups in Th2-associated CCR3 receptors. Western blot analysis showed that by comparison with controls, hypersplenic rats had higher levels of CXCR3 and CCR5 protein but lower levels of CCR3 protein. CONCLUSIONS: The abnormal expression of Th1-associated chemokine receptors in spleens of rats with cirrhosis and hypersplenism induced by CCL4 suggests that a functional imbalance between Th1/Th2 cells may play a role in the pathogenesis of hypersplenism.